Effect of cutting position and vine pruning level on growth and yield of sweet potato (ipomoea batatas l.) - Munetsi, Moreproof (2017)
There is yawning variation in yield of storage roots and vines of sweet potato (Ipomoea batatas) among farmers due to the use of different cutting positions and pruning of vines at different levels. Therefore, the aim of this study was to establish the cutting position and the vine pruning level that give the highest yield of both the storage roots and vines. Determination of storage root length, central storage root diameter, storage root weight and vine weight among different cutting positions and vine pruning levels was the objective of the study. The study was conducted in a 3x3 factorial arrangement in randomized complete block design (RCBD) with three replications. Factor 1 was cutting position and it had three levels (apical cutting, middle cutting and basal cutting). Factor 2 was pruning level and it had three levels (0, 25 and 50%). Twenty-seven ridges were aptly constructed using a spade. Length, width and height of each ridge were measured 120, 50 and 40 cm respectively. Vine weight was measured at 50 days after planting (vine pruning day) and 100 days after planting (storage root harvesting day) and added to make total weight. Storage root length, diameter and weight were measured at 100 days after planting. Data was analysed using GenStat version 14 and mean separation was done using the least significance difference (LSD) at 5% significance level. Storage root length indicated significant difference (p<0.001) only among cutting positions with highest mean length (16.2 cm/root) obtained from apical cutting and the lowest (11.98 cm/root) from basal cutting. Cutting position and pruning level interacted significantly (p<0.05) to affect differences in storage root diameter, storage root weight and vine weight. Highest mean root diameter and root weight were obtained from middle cutting and 25% vine pruning level, with the lowest being obtained from basal cutting and 50% vine pruning level. Highest vine weight was recorded from middle cutting and 50% vine pruning level, with the lowest being recorded from basal cutting and 0% vine pruning level. Both middle and apical stem cuttings can be recommended for higher storage root and vine yield. Vine pruning at 25% can be recommended for higher storage root yield while pruning at 50% can be suggested for higher vine yield. Therefore, the study came up with the solution for shortage of planting material since both apical and middle cuttings gave higher and not significantly different root diameter, root weight and vine weight that both can be planted rather than planting apical cuttings only.